Pengaruh Aplikasi Skigrem (Smart Kids With Great Media) Terhadap Kemampuan Menyimak Pada Anak Usia 5-6 Tahun Di TK Pautan Hati Kabupaten Sijunjung Sumatera Barat - Fitrah Qalbina; Zulkifli N; Rita Kurnia (Journal on Education, 2024)
The Skigrem (smart kids with great media) application aims to determine the listening abilities of children aged 5-6 years before and after being treated with the Skigrem application at Pautan Hati Kindergarten, Sijunjung Regency, West Sumatra. This type of research is experimental research using a one group pretest-posttest design model.The research population was 11 children aged 5-6 years at Pautan Hati Kindergarten, Sijunjung Regency, West Sumatra. The sample used was all children, namely 11 children. The data analysis technique used is the t test. Based on the results of the research that has been carried out, the researchers concluded that children's listening ability before being given treatment was 38.64%, then after being given treatment in class increased by a percentage of 75.00%. Based on the test results, it is known that there is an influence of the skigrem application (smart kids with great media) on the listening ability of children aged 5-6 years at Pautan Hati Kindergarten, Sijunjung Regency, West Sumatra.